2017
DOI: 10.3389/fmed.2017.00237
|View full text |Cite
|
Sign up to set email alerts
|

Karate and Dance Training to Improve Balance and Stabilize Mood in Patients with Parkinson’s Disease: A Feasibility Study

Abstract: The present pilot study investigated the effect of karate (according to the rules of the German Karate Federation) and dance training compared to an inactive control group in patients with Parkinson’s disease (PD). 65 patients were recruited. At the end, 37 patients completed the post-test. From those 37 patients, 16 had chosen the karate training, 9 the dance training and 12 the waiting control group. Before and after the whole training phase cognitive performance, emotional well-being and balance were measur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 31 publications
1
35
0
1
Order By: Relevance
“…The effectiveness of martial arts training in improving balance was previously confirmed by other researchers as well. dahmen-Zimmer and Jansen [20] examined 37 pa- The present research revealed an improvement in the dynamic strength test, which indicated longer distance jumps. Statistical significance was observed in the groups of girls with normal and excess body weight, as well as in the group of overweight boys.…”
Section: Discussionsupporting
confidence: 53%
“…The effectiveness of martial arts training in improving balance was previously confirmed by other researchers as well. dahmen-Zimmer and Jansen [20] examined 37 pa- The present research revealed an improvement in the dynamic strength test, which indicated longer distance jumps. Statistical significance was observed in the groups of girls with normal and excess body weight, as well as in the group of overweight boys.…”
Section: Discussionsupporting
confidence: 53%
“…The ten-week duration of the trial itself likely rendered measurable change in these domains highly unlikely, compounded by the study being underpowered. Improvements have been seen in such domains in prior karate studies, albeit of longer duration [10,12].…”
Section: Plos Onementioning
confidence: 93%
“…despite achievement of individually-set goals and improvement in quality of life, objective benefits were not demonstrated. In a recent German pilot study comparing weekly karate vs. dance among individuals with PD, participants self-selected into karate training, dance training, or a sedentary control group, with 16, 9, and 12 participants in each, respectively [12]. Dahmen-Zimmer et al highlighted the feasibility of conducting karate classes with PD patients and reported high adherence as a marker of high acceptability.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…A PubMed search for clinical trials that measured happiness, well-being, or self-compassion in persons with PD only yielded several small studies: none used self-compassion, one used happiness [26], and ten used well-being as an outcome [27][28][29][30][31][32][33][34][35][36] (see Table 1 for more information). Well-being and happiness measurements were used as a primary outcome in five [27,28,30,33,35] out of eleven clinical trials. Moreover, well-being outcomes were often claimed to be measured, while the scores were derived from QoL questionnaires and not from specific well-being questionnaires.…”
mentioning
confidence: 99%